The prognostic value of cardiopulmonary exercise testing in interstitial lung disease: a systematic review. Issue 3 (17th August 2020) - Barratt, Shaney L.; Davis, Richard; Sharp, Charles; Pauling, John D.
The heterogeneity of interstitial lung disease (ILD) results in prognostic uncertainty concerning end-of-life discussions and optimal timing for transplantation. Effective prognostic markers and prediction models are needed. Cardiopulmonary exercise testing (CPET) provides a comprehensive assessment of the physiological changes in the respiratory, cardiovascular and musculoskeletal systems in a controlled laboratory environment. It has shown promise as a prognostic factor for other chronic respiratory conditions. We sought to evaluate the prognostic value of CPET in predicting outcomes in longitudinal studies of ILD. MEDLINE, Embase and the Cochrane Database of Systematic Reviews were used to identify studies reporting the prognostic value of CPET in predicting outcomes in longitudinal studies of ILD. Study quality was assessed using the Quality in Prognosis Study risk of bias tool. Thirteen studies were included that reported the prognostic value of CPET in ILD. All studies reported at least one CPET parameter predicting clinical outcomes in ILD, with survival being the principal outcome assessed. Maximum oxygen consumption, reduced ventilatory efficiency and exercise-induced hypoxaemia were all reported to have prognostic value in ILD. Issues with study design (primarily due to inherent problems of retrospective studies, patient selection and presentation of numerous CPET parameters), insufficient adjustment for important confounders and inadequate statistical analyses limit the strength of the conclusions that can be drawn at this stage. There is insufficient evidence to confirm the value of CPET in facilitating "real-world" clinical decisions in ILD. Additional prospective studies are required to validate the putative prognostic associations reported in previous studies in carefully phenotyped patient populations. There is presently insufficient evidence to confirm the value of CPET in facilitating "real-world" clinical decisions in ILD. Additional prospective studies are required to validate the putative prognostic associations reported in previous studies. https://bit.ly/3dfp5kq